Analysis of polyphenols in Aegle marmelos leaf and ameliorative efficacy against diabetic mice through restoration of antioxidant and anti‐inflammatory status. Issue 4 (11th July 2021) - Ibrahim, Mohammad; Parveen, Bushra; Zahiruddin, Sultan; Gautam, Gaurav; Parveen, Rabea; Khan, Mohammad Ahmed; Gupta, Arun; Ahmad, Sayeed
Abstract: The biomedical survey reports edible plant Aegle marmelos has been utilized for centuries by tribal communities in India as a dietary supplement for the management of diabetes. Herein, we have investigated cytotoxicity, cytoprotective and antidiabetic activity of characterized alkaloid‐free hydroalcoholic extract of A. marmelos (AFEAM; 200 and 400 mg/kg). Identification of polyphenols and quantification of major compounds were done using UPLC‐MS and HPTLC, respectively. AFEAM showed good cytocompatibility and cytoprotective potential against oxidative stress induced by hyperglycemia in HepG2 cells. The AFEAM intake had significantly ameliorated the serum blood glucose level, state of dyslipidemia, level of pro‐inflammatory markers (tumor necrosis factor‐α, interleukin‐6, and interleukin‐1β), and antioxidant (superoxide dismutase, catalase, glutathione peroxidase, and malondialdehyde) status in diabetic mice. Histological examination of the treated groups showed amelioration of damaged pancreas, liver, and kidney tissues. Conclusively, AFEAM intake might be promising dietary supplements for prediabetics as well as an adjuvant to modern treatment in diabetics. Practical applications: Different reports have been published on Aegle marmelos but as per our understanding till date, no study has been reported on the amelioration of diabetes due to alkaloid free hydroalcoholic extract of A. marmelos /polyphenolic content in the animal model. The result of this study indicated that A. marmelos supplementation effectively ameliorates diabetes through the restoration of antioxidant and anti‐inflammatory status. This study has collated sufficient scientific evidence for the dietary application of A. marmelos in society especially for prediabetics, however, it can also be used as an adjuvant to modern treatments in diabetics. Abstract : Evaluation of cytotoxicity, cytoprotective and antidiabetic activity of AFEAM using in vitro and in vivo approached and also explored phytochemical profiling using UPLC‐MS and HPTLC, respectively.